Quality of Prenatal Care and Associated Factors among Pregnant Women at Public Health Facilities of Wogera District, Northwest Ethiopia - Asrat Kassaw; Ayal Debie; Demiss Mulatu Geberu (Hindawi Limited, 2020)
Background. Prenatal care refers to services a pregnant woman receives during pregnancy to ensure a healthy outcome for herself and her newborn. However, only limited studies have so far been done to assess the quality of prenatal care in the study area. Thus, this study is aimed at assessing the quality of prenatal care and associated factors at public health facilities in Wogera district, northwest Ethiopia. Methods. An institution-based cross-sectional study was conducted in Wogera district from March to April 2019. A total of 465 pregnant women were interviewed using a semi-structured interviewer-administered questionnaire; consecutive sampling was used to select the participants. The binary logistic regression analysis model was fitted to identify the potential predictor variables. Variables with <0.2 p values were fitted into the multivariable logistic regression analysis model; <0.05 p values and an adjusted odds ratio (AOR) with a 95% confidence interval (CI) were used to declare factors associated with the quality of prenatal care. Results. The overall quality of prenatal care was 32.7% (95% CI: 28.1, 37.2). Four or more prenatal care visits (AOR=2.3; 95% CI: 1.2, 4.7), high maternal education (AOR=2.9; 95% CI: 1.03, 7.93), over USD 175.5 monthly household income (AOR=2.8; 95% CI: 1.1, 7.8), and the availability of maternity waiting areas (AOR=2.4; 95% CI: 1.2, 5.0) were positively associated with the quality of the care. Conclusion. The overall quality of prenatal care in this study was low. Therefore, promoting focused prenatal care and increasing infrastructure, encouraging maternal education, and compensating for the healthcare costs for women with low household income might enhance the quality of the care.